2018
DOI: 10.3892/mmr.2018.8700
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tetrahydropalmatine against ketamine-induced learning and memory injury via antioxidative, anti-inflammatory and anti-apoptotic mechanisms in mice

Abstract: Tetrahydropalmatine exerts numerous pharmacological activities, including analgesic and narcotic effects; anti-arrhythmic, blood pressure lowering and cardioprotective effects; protective effects against cerebral ischemia-reperfusion injury; inhibition of platelet aggregation; prevention of ulcerative diseases and inhibition of gastric acid secretion; antitumor effects; and beneficial effects on the withdrawal symptoms associated with drug addiction. The present study aimed to investigate the protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Inflammatory cytokines such as TNF- α and IL-6 play essential roles in the pathogenesis of ConA-induced liver injury [3, 26]. L-THP had anti-inflammatory effect by downregulating the expression of the inflammatory cytokines TNF- α and IL-6 [19, 27, 28]. However, function of L-THP pretreatment in ConA-induced AIH remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines such as TNF- α and IL-6 play essential roles in the pathogenesis of ConA-induced liver injury [3, 26]. L-THP had anti-inflammatory effect by downregulating the expression of the inflammatory cytokines TNF- α and IL-6 [19, 27, 28]. However, function of L-THP pretreatment in ConA-induced AIH remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Wang which has been widely used in traditional Chinese medicine for treating various pains and cardiovascular disease (Han et al, 2012; Kang et al, 2016). Previous studies have indicated that THP presented multiple pharmacological effects on cardio and neural tissues, such as cardioprotection, neuroprotection, anti-oxidant, anti-apoptosis, and anti-inflammation (Wu et al, 2010; Zhang et al, 2015, 2018). THP improved memory impairment, protected the blood brain barrier and cerebral ischemia-reperfusion injuries in experimental mice models (Mao et al, 2015; Cao et al, 2018; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yuanhuzhitong prescription comprised of Rhizoma Corydalis and A. dahurica could relieve various pains through activating or blocking the G-coupled protein receptors (GCPRs) such as 5-HT1A, OPRM1, ADRB2 receptors and block D 2 receptor which are mainly located in the central nervous system 25 . TDE, with bitter property, accounts for the main analgesic activity of Yuanhuzhitong prescription by blocking dopamine receptors in the central nervous system and depleting dopamine within the brain 26 , 27 . It was suggested that the TDE suppressed pain mainly within the brain region, so it is necessary for TDE to keep a certain concentration in the brain 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%